NEW APPROACH TO DETERMINING OF COMPRESSED AIR TANK MINIMAL VOLUME - Mitar Perušić; Branko Pejović; Radislav Filipović; Milenko Smiljanić; Mirko Radić (Journal of Engineering & Processing Management, 2016)
Based on relations for the maximum work at the closed thermodynamic system, the paper presents implementation of a general model for determining the minimum storage volume for compressed air. Due to the mechanical and thermodynamic imbalance of observed model, there are the conditions for obtaining the maximum work. Derived relations, which represent a new model, can be directly used in technical practice for the case that are known parameters that define the initial state in the reservoir, the parameters of the environment, and energy to get from the compressed air. For a complete presentation of the reporting process, it is presented in the working p-v and thermal T-s diagram. In addition to the screening, the paper presents and graphic design of the problem, which can also be used to control of the results. Also, it is illustrated the application of the model on a practical case, where a certain minimum volume of the storage tank filled with air.
Keywords: air; process; tank; thermodynamics imbalance; volume